Step * 1 1 of Lemma get_face_wf

.....assertion..... 
1. CubicalSet
2. Cname List
3. ∀[J:nameset(I) List]. ∀[x:nameset(I)]. ∀[i:ℕ2].
     ∀bx:open_box(X;I;J;x;i). ∀y:nameset(J). ∀c:ℕ2.
       (filter(λf.((dimension(f) =z y) ∧b (direction(f) =z c));bx)
       []
       ∈ ({f:{f:I-face(X;I)| (f ∈ bx)} | ↑((dimension(f) =z y) ∧b (direction(f) =z c))}  List)))
4. Cname List
5. nameset(I)
6. : ℕ2
7. box open_box(X;I;J;x;i)
8. nameset(J)
9. : ℕ2
⊢ J ∈ nameset(I) List
BY
(DVar `box' THEN SubsumeC ⌜nameset(J) List⌝ ⋅}

1
1. CubicalSet
2. Cname List
3. ∀[J:nameset(I) List]. ∀[x:nameset(I)]. ∀[i:ℕ2].
     ∀bx:open_box(X;I;J;x;i). ∀y:nameset(J). ∀c:ℕ2.
       (filter(λf.((dimension(f) =z y) ∧b (direction(f) =z c));bx)
       []
       ∈ ({f:{f:I-face(X;I)| (f ∈ bx)} | ↑((dimension(f) =z y) ∧b (direction(f) =z c))}  List)))
4. Cname List
5. nameset(I)
6. : ℕ2
7. box I-face(X;I) List
8. adjacent-compatible(X;I;box)
∧ (x ∈ J))
∧ l_subset(Cname;J;I)
∧ ((∀y:nameset(J). ∀c:ℕ2.  (∃f∈box. face-name(f) = <y, c> ∈ (nameset(I) × ℕ2)))
  ∧ (∃f∈box. face-name(f) = <x, i> ∈ (nameset(I) × ℕ2))
  ∧ (∀f∈box.¬(face-name(f) = <x, i> ∈ (nameset(I) × ℕ2))))
∧ (∀f∈box.(fst(f) ∈ [x J]))
∧ (∀f1,f2∈box.  ¬(face-name(f1) face-name(f2) ∈ (nameset(I) × ℕ2)))
9. nameset(J)
10. : ℕ2
⊢ J ∈ nameset(J) List

2
1. CubicalSet
2. Cname List
3. ∀[J:nameset(I) List]. ∀[x:nameset(I)]. ∀[i:ℕ2].
     ∀bx:open_box(X;I;J;x;i). ∀y:nameset(J). ∀c:ℕ2.
       (filter(λf.((dimension(f) =z y) ∧b (direction(f) =z c));bx)
       []
       ∈ ({f:{f:I-face(X;I)| (f ∈ bx)} | ↑((dimension(f) =z y) ∧b (direction(f) =z c))}  List)))
4. Cname List
5. nameset(I)
6. : ℕ2
7. box I-face(X;I) List
8. adjacent-compatible(X;I;box)
∧ (x ∈ J))
∧ l_subset(Cname;J;I)
∧ ((∀y:nameset(J). ∀c:ℕ2.  (∃f∈box. face-name(f) = <y, c> ∈ (nameset(I) × ℕ2)))
  ∧ (∃f∈box. face-name(f) = <x, i> ∈ (nameset(I) × ℕ2))
  ∧ (∀f∈box.¬(face-name(f) = <x, i> ∈ (nameset(I) × ℕ2))))
∧ (∀f∈box.(fst(f) ∈ [x J]))
∧ (∀f1,f2∈box.  ¬(face-name(f1) face-name(f2) ∈ (nameset(I) × ℕ2)))
9. nameset(J)
10. : ℕ2
11. J ∈ (nameset(J) List)
⊢ (nameset(J) List) ⊆(nameset(I) List)


Latex:


Latex:
.....assertion..... 
1.  X  :  CubicalSet
2.  I  :  Cname  List
3.  \mforall{}[J:nameset(I)  List].  \mforall{}[x:nameset(I)].  \mforall{}[i:\mBbbN{}2].
          \mforall{}bx:open\_box(X;I;J;x;i).  \mforall{}y:nameset(J).  \mforall{}c:\mBbbN{}2.
              (\mneg{}(filter(\mlambda{}f.((dimension(f)  =\msubz{}  y)  \mwedge{}\msubb{}  (direction(f)  =\msubz{}  c));bx)  =  []))
4.  J  :  Cname  List
5.  x  :  nameset(I)
6.  i  :  \mBbbN{}2
7.  box  :  open\_box(X;I;J;x;i)
8.  y  :  nameset(J)
9.  c  :  \mBbbN{}2
\mvdash{}  J  \mmember{}  nameset(I)  List


By


Latex:
(DVar  `box'  THEN  SubsumeC  \mkleeneopen{}nameset(J)  List\mkleeneclose{}  \mcdot{})




Home Index